STRATEGI KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA DALAM MELESTARIKAN FESTIVAL BUNGA DAN BUAH DI KABUPATEN KARO - Bonawati Mahardika; Elok Perwirawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study discusses the communication strategy used by the Culture and Tourism Office in succeeding the flower and fruit festival in Karo Regency. This is a descriptive qualitative research. The techniques of collecting data are using the method of observation and in-depth interviews with research informants and using literature or documents that support research. Descriptive analysis results show that the communication strategy carried out by the Culture and Tourism Office in terms of the target audience strategy still prioritizes the local community. As for the message packaged strategy, it can be seen that there are efforts to improve the types of events and collaborative efforts with third parties to enliven the event. But the Office is still not optimal in conducting To Establish Acceptance, or controlling or ensuring messages are well received from related parties, such as regarding the smooth transportation to the event center. This can be seen from the total congestion that hit, so that many visitors did not arrive at the Flower and Fruit Festival. From the media strategy, the government should increase the use of diverse and targeted media and collaborate with travel agents so as to be able to provide extensive and persuasive information, especially for foreign tourists.